Differences in primary sites of infection between zoonotic and human tuberculosis: Results from a worldwide systematic review - Durr, S.; Muller, B.; Alonso, Silvia; Hattendorf, J.; Laisse, C.J.M.; Helden, P.D. van; Zinsstag, Jakob (Public Library of Science, 2013)
Tuberculosis (TB) is one of the most devastating infectious diseases worldwide. Whilst global burden estimates for M. tuberculosis infection (MtTB) are well established, accurate data on the contribution of zoonotic TB (zTB) caused by M. bovis or M. caprae to human TB are scarce. The association of M. bovis infection with extrapulmonary tuberculosis has been suggested repeatedly, though there is little scientific evidence available to support this relationship. The present study aimed to determine globally the occurrence of extrapulmonary TB and the primary site (i.e. primary body location affected) of zTB in comparison with MtTB, based on previously published reports. A systematic literature review was conducted in 32 different bibliographic databases, selecting reports on zTB written in English, French, German, Spanish or Portuguese. Data from 27 reports from Africa, America, Europe and the Western Pacific Region were extracted for analyses. Low income countries, in Africa and South-East Asia, were highly underrepresented in the dataset. The median proportion of extrapulmonary TB cases was significantly increased among zTB in comparison with data from registries of Europe and USA, reporting mainly MtTB cases (47% versus 22% in Europe, 73% versus 30% in the USA). These findings were confirmed by analyses of eight studies reporting on the proportions of extrapulmonary TB in comparable populations of zTB and MtTB cases (median 63% versus 22%). Also, disparities of primary sites of extrapulmonary TB between zTB and MtTB were detected. Our findings, based on global data, confirm the widely suggested association between zTB and extrapulmonary disease. Different disability weights for zTB and MtTB should be considered and we recommend separate burden estimates for the two diseases.